Chapter 18. Tomato Production: VPH ch. 18, CV137/HS739, rev. 6/2024 - Frey, Craig; Kanissery, Ramdas; Qureshi, Jawwad; Desaeger, Johan; Vallad, Gary E. (EDIS, 2024)
Chapter 18 of the Vegetable Production Handbook of Florida